Retrospective self-gating for single-petal rosette trajectory in 2D lung imaging - Frantz, Hanna; Rasche, Volker (Frontiers in Physics, 2025)
PurposeTo investigate the performance of retrospective self-gating techniques in combination with the single-petal rosette (SPR) trajectory for 2D imaging of the lung.MethodsEight healthy volunteers underwent free-breathing and breath-hold MRI using the single-petal rosette trajectory (SPR), as well as radial UTE acquisition combined with the tiny golden angle acquisition scheme. Retrospective self-gating techniques (k-space based, image based and nuSG) were used for reconstruction with temporal resolutions of 50, 75 and 100 ms. The SPR trajectory was compared with the conventional radial UTE technique regarding image sharpness and signal-to-noise ratio (SNR) for all investigated resolutions.ResultsLow-spatial high-temporal resolution images used for image-based self-gating techniques benefit from more the efficient k-space sampling pattern of SPR. Image sharpness values are lower for SPR compared with radial UTE for all temporal resolutions but especially prominent for 75 ms temporal resolution. The same was found for SNR, where the highest increase was found for a temporal resolution of 75 ms.ConclusionExploiting the higher efficiency in k-space sampling of the full-petal SPR for image based self-gating can be a means of decreasing temporal resolution.